Rapidly Growing Gastrointestinal Stromal Tumor on the Esophagus - Ji Hye Park; Sung Eun Kim; Seun Ja Park; Moo In Park; Won Moon; Jae Hyun Kim; Kyoungwon Jung; Myung Hun Lee (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Gastrointestinal stromal tumors (GISTs) are rare mesenchymal neoplasms that mainly occur in the stomach and small intestine; those arising in the esophagus are rarer. A 54-year-old woman was referred to our hospital with a one-month history of dysphagia. Esophagogastroduodenoscopy (EGD), performed approximately five months earlier, had not revealed any specific findings. However, an EGD performed in our hospital showed the presence of a round, protruding lesion (approximately 40×30 mm in size), with a normal overlying mucosal surface, 35–39 cm from the upper incisor. Chest computed tomography (CT) revealed a large esophageal mass. Enucleation was performed on the esophageal mass, and a GIST was diagnosed using immunochemical staining. Imatinib mesylate administration was initiated two months postoperatively. The patient was stable, without any evident recurrence in the 8-month postoperative follow-up EGD and chest CT examinations. Therefore, physicians should consider that patients with worsening dysphagia may have an underlying organic condition, such as an acute increase in size of an esophageal GIST, even if recent examinations were unremarkable.